Grande amor romântico: evidências psicométricas e contribuições psicossociais - Freitas, Nájila Bianca Campos (2020)
Great romantic love is about expectations of how a loving relationship should form, develop, function and be maintained, at least ideally. The thesis addresses this issue by proposing the hypothesis that beliefs about great romantic love are anchored in individual and social psychological variables.To verify this hypothesis, the following studies were counted: In Study 1, theoretical in nature, it was sought to introduce the theme of beliefs about great romantic love and, thus, identify the criteria that it is composed of, based on more widespread theoretical models of Social Psychology on loving relationships. In Study 2 (N = 276), of a quantitative nature, it was developed a measure (Great Romantic Love Belief Scale ) that gathered satisfactory psychometric evidence of factorial and convergent validity (dark triad, virtuous personality, human values and well-being), in addition to internal consistency. The Exploratory Factor Analysis resulted in a single factor where KMO = 0.64 and Bartlett sphericity χ² (6) = 296.5; p <0.001), a satisfactory adequacy index (CFI = 0.99) was observed, with a eigenvalue of 2.18, explained variance of 54.0% and internal consistency index of 0.84. ECGAR was correlated to traits of Machiavellianism (r = -0.15), psychopathy (r = -0.23), with the normative (r = 0.35) and interactive (r = 0.17) valuative subfunctions and the variables of well-being and satisfaction with life (r = 0.13), positive affects (r = 0.17), positivity (r = 0.22), vitality (r = 0.22) and negative affects (r = -0.20, p <0.01). Of these, ECGAR was predicted by psychopathy [adjusted R² = 0.05; F (1.263) = 14.88; p = 0.001] normative sub-function [adjusted R² = 0.12; F (1.263) = 35.66; p = 0.001] and positivity [adjusted R² = 0.05; F (1.263) = 13.96; p = 0.001]. In study 3 (N = 391), quantitative in nature, the objective was, in turn, to test the effects of the Triangular Love Scale (intimacy, passion and commitment) on beliefs about great romantic love, mediated by social values. A moderating effect of social values on the ETA_Total relation to ECGAR was then proven (β = 0.20, t = 2.07, p = 0.039), it was also found that the more people are guided by social values, the greater the interaction between ETA and ECGAR. Therefore, it is concluded that the understanding about beliefs on great romantic love favors knowledge of the components that comprise it, as well as the psychosocial variables that interfere in their formation. Given this, it makes it possible to understand how romantic relationships are formed prior to their formation and, accordingly, carry out interferences that prevent or stimulate mechanisms to optimize a healthy and lasting relationship.